Making Parallel Programs Reliable with Stable Multithreading. - JUNFENG YANG; HEMING CUI; JINGYUE WU; GANG HU; YANG TANG (Communications of the ACM, 2014)
The article discusses the use of stable multithreading programs in relation to various efforts to make parallel programs more reliable as of March 2014, focusing on several research and development (R&D) breakthroughs regarding improvements to the reliability of sequential computer software programs. Computer company Microsoft Corp.'s Static Driver Verifier program is mentioned, along with technology trends and information on certified operating systems and compilers. Multicore computer processors, big-data analytics, and online social networking are examined.